ANSWER
x = -2 and x = 6
Step-by-step explanation
The rate of change of the function is the derivative of the function.
In this case, we have the function,
![y=(1)/(2-x)=(2-x)^(-1)](https://img.qammunity.org/2023/formulas/mathematics/college/5yb3e0a7i5z5natxdyjd36gs6uic4ucj3y.png)
Using the chain rule,
![f^(\prime)(u(x))=f^(\prime)(u)\cdot u^(\prime)(x)](https://img.qammunity.org/2023/formulas/mathematics/college/cu9yr2o1x4l7i38uafgukfpdollgzq5fzh.png)
In this case, u = 2 - x and f(u) is u⁻¹,
![y^(\prime)=-1\cdot(2-x)^(-1-1)\cdot(-1)=(2-x)^(-2)](https://img.qammunity.org/2023/formulas/mathematics/college/ed7uwp0osmmqsmv9zgi13mob5f7yy4s7l8.png)
The rate of change is,
![y^(\prime)=(1)/((2-x)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/l1fobw7e46afri7wkip8it6nznpynnl14f.png)
We have to find for which values of x, y' = 1/16. Thus, we have to solve the equation,
![(1)/(16)=(1)/((2-x)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/f90ubwjibosmp3781iylwfz6x0seijuc1d.png)
Raise both sides to the exponent -1 - i.e. flip both sides of the equation,
![(2-x)^2=16](https://img.qammunity.org/2023/formulas/mathematics/college/1uiy2sxy3jhvssboo88mcqpjphle5eauhb.png)
Take the square root of both sides - remember that the square root has a negative and a positive result,
![\begin{gathered} \sqrt[]{(2-x)^2}=\pm\sqrt[]{16} \\ \\ 2-x=\pm4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qxbxm92zn0ycyo7gqmtggmblbb8m000trp.png)
Subtract 2 from both sides,
![\begin{gathered} 2-2-x=-2\pm4 \\ \\ -x=-2\pm4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/osdoh7h70d85p7qbpd7ks6b1kfyxr3xo12.png)
And multiply both sides by -1,
![x=2\pm4](https://img.qammunity.org/2023/formulas/mathematics/college/kpi3ikfp9jge04ye9on3h6mnawcvdrpa44.png)
Hence, the values of x for which the rate of change of y with respect to x is equal to 1/16 are x = -2 and x = 6